Mechanisms Linking Olfactory Impairment and Risk of Mortality - Van Regemorter, Victoria; Hummel, Thomas; Rosenzweig, Flora; Mouraux, André; Rombaux, Philippe; Huart, Caroline (Frontiers in Neuroscience, 2020)
Olfaction is a sense involved in a complex set of tasks, influencing eating behavior, increasing awareness of environmental hazards and affecting social communication. Surprisingly, smell disorders are very frequent, especially in the elderly population. Several recent studies conducted mostly in older subjects have demonstrated a strong association between olfactory impairment and overall mortality risk, with anosmia being even more predictive of 5-years mortality risk than cardiovascular disease. Presently, the underlying pathophysiology linking olfactory impairment to mortality remains unknown and only putative mechanisms are suggested. This review aims to examine the link between olfactory impairment and mortality and to discuss existing ideas on underlying existing mechanisms including, (1) the effect of olfactory loss on nutrition, life-threatening situations and social interactions, (2) associated neurodegenerative diseases, (3) accelerated brain aging and (4) reflection of general health status being reflected in olfactory function.